2003
DOI: 10.1177/13670069030070020101
|View full text |Cite
|
Sign up to set email alerts
|

The Modeling Hypothesis and child bilingual codemixing

Abstract: According to one explanation of child bilingual codemixing (the modeling hypothesis), bilingual children' s rates of mixing are related to rates of mixing in the input addressed to them. An assumption of this hypothesis is that bilingual children are sensitive to codemixing in the input and that they can adjust their own rates on-line in accordance with the input. Despite its widespread appeal, evidence concerning its validity has been largely inconclusive. The assumption is largely noncontroversial in the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 17 publications
5
77
1
1
Order By: Relevance
“…For this study, discourse context was interpreted as being the 282 The International Journal of Bilingual Education and Bilingualism adult interlocutor's language choice, which is in line with the assumptions of much prior work (e.g. Comeau et al ., 2003;Genesee et al ., 1995a;Lanza, 1997;Nicoladis & Secco, 2000). Because the children varied in terms of the typical contexts and interlocutors where and with whom they would use each language, it was deemed appropriate to choose the interlocutor for each language session based on each child's background, resulting in different arrangements across children.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…For this study, discourse context was interpreted as being the 282 The International Journal of Bilingual Education and Bilingualism adult interlocutor's language choice, which is in line with the assumptions of much prior work (e.g. Comeau et al ., 2003;Genesee et al ., 1995a;Lanza, 1997;Nicoladis & Secco, 2000). Because the children varied in terms of the typical contexts and interlocutors where and with whom they would use each language, it was deemed appropriate to choose the interlocutor for each language session based on each child's background, resulting in different arrangements across children.…”
Section: Methodsmentioning
confidence: 97%
“…Simultaneous bilingual children can use their languages differentially and with sensitivity to their interlocutor's language choice by the age of 2 years (Comeau et al ., 2003;Deuchar & Quay, 2000;Genesee et al ., 1995aGenesee et al ., , 1997Lanza, 1997;. Interlocutor sensitivity is often defined as children using more of their language A with an interlocutor who speaks language A, and more of their language B with an interlocutor who speaks language B (e.g.…”
mentioning
confidence: 99%
“…Goodz, 1994;Genesee et al, 1995;Genesee et al, 1996) claimed no correlation between parents' mixing rate and children's mixing rate, whereas the findings of Comeau et al (2003) study demonstrated that bilingual children changed their mixing rate in accordance with that of the interlocutors.…”
Section: Discussionmentioning
confidence: 62%
“…Additional evidence from our lab that young bilingual children are sensitive and responsive to unfamiliar interlocutors' language preferences comes from a study by Comeau, Genesee and Lapaquette (2003). Comeau et al observed six Montreal French-English bilingual 2-to 2 ½ year olds while they played with an unfamiliar experimenter on three separate occasions.…”
Section: Can Bilingual Children Regulate Their Code-mixing With Unfammentioning
confidence: 79%